Adipocyte Fatty Acid–Binding Protein as a Predictor of Outcome in Alcohol-induced Acute-On-Chronic Liver Failure - Kulkarni, Anand V. (J Clin Exp Hepatol, 2021)
BACKGROUND: Alcohol is the leading cause of acute-on-chronic liver failure (ACLF). Several severity scores predict the outcome of ACLF. However, there is a lack of simple biomarkers in predicting the outcome of these sick patients. Fatty acid–binding proteins (FABPs) are small cytosolic proteins that play a major role in lipid metabolism, energy homeostasis, and inflammation, but, have not been investigated in alcohol-induced ACLF (A-ACLF). OBJECTIVES: The primary objective was to assess the correlation between serum adipocyte-FABP (A-FABP) and liver-FABP (L-FABP) levels on mortality at day 90. Secondary objectives were to compare the levels between controls and A-ACLF, correlate L-FABP, and A-FABP levels on the development of organ failure/sepsis at day 90. METHODS: In this prospective observational pilot study, we included patients with A-ACLF and age-matched healthy controls. FABP's were analyzed by enzyme-linked immunosorbent assay method. The patients were followed up for 90 days. RESULTS: Twenty-five patients with A-ACLF (mean age: 40years; mean model for end-stage liver disease NA: 29.8; median Modified Maddrey's discriminant function [mDF]: 95) and 12 controls (mean age: 36.83yrs) were included in the study. A-FABP and L-FABP levels were significantly high in patients with A-ACLF than controls. Forty-four percent of patients with A-ACLF developed sepsis, 48% developed organ failure, and 44% expired by day 90. On multivariate Cox regression analysis, A-FABP (hazard ratio [HR]: 1.27 [1.08–1.5]; P = 0.003), Asian Pacific Association for the Study of Liver ACLF research consortium score (HR: 3.3[1.15–9.54]; P = 0.02), L-FABP (HR: 0.69 [0.52–0.91]; P = 0.009), and serum protein levels (HR: 0.03 [0.003–0.36]; P = 0.005) predicted mortality. A-FABP (1.17 [1.07–1.29]; P = 0.001), and serum bilirubin (1.05 [0.99–1.12]; P = 0.06) predicted development of organ failure, and only mDF (HR: 1.04 [1.01–1.07]; P = 0.009) predicted the development of sepsis on multivariate analysis. Fifteen patients received steroid therapy, of which 13.34% were nonresponders. CONCLUSIONS: In a selected group of patients with A-ACLF, A-FABP is highly sensitive at predicting mortality and outcome. If validated in a large, diverse sample, A-FABP can be used as a simple biomarker for prognostication in A-ACLF.